2018
DOI: 10.1016/j.actbio.2018.01.042
|View full text |Cite
|
Sign up to set email alerts
|

Polyisocyanopeptide hydrogels: A novel thermo-responsive hydrogel supporting pre-vascularization and the development of organotypic structures

Abstract: Molecular and mechanical interactions with the surrounding environment are essential for cell functions. Although 2D culture systems greatly contributed to our understanding of complex biological phenomena, they cannot substitute for crucial interaction that take place in 3D. 3D culture systems aim to overcome limitations of the 2D cultures and answer new questions about cell functions. Thermo-responsive biomimetic polyisocyanopeptide (PIC) hydrogels are promising new candidates for 3D cell, tissue, and organ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 47 publications
2
65
0
Order By: Relevance
“…However, care must be taken to control gel stiffness because this parameter can affect stem cell differentiation. [14][15][16] Interestingly, we reported that pluripotent embryonic human stem cells enter stasis (i.e. the G 0 state of the cell cycle) if immersed as colonies within a new type of extremely so wholly synthetic hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…However, care must be taken to control gel stiffness because this parameter can affect stem cell differentiation. [14][15][16] Interestingly, we reported that pluripotent embryonic human stem cells enter stasis (i.e. the G 0 state of the cell cycle) if immersed as colonies within a new type of extremely so wholly synthetic hydrogel.…”
Section: Introductionmentioning
confidence: 99%
“…Soft, structural biomacromolecules and their synthetic analogues that self-associate into two- and three-dimensional structures such as membranes and hydrogels forming cellular structures 20 , 21 and interstitial fluid components, respectively, 22 − 24 have been the focus of our research for a number of years. More recently, they have been applied as coatings and delivery agents for therapeutic 25 and device applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in blood contact applications, such as those reported previously from our laboratory, the degree of antifouling nature and oxygen permeability are both critical to functionality, whereas an intersitial application requires a certain degree of biointegration; this is achieved by tuning both the base material properties and selecting the appropriate peripheral functionalities from a library of monomers. 24 , 28 The polysaccharide material employed in this report not only forms a hydrogel-like network encapsulating the sensor that acts as a barrier between the metal surface and the soft tissue of the eye, but also acts to stabilize and prevent enzyme migration out of the coating, while allowing for free diffusion of the analyte into the coating. 27 − 29 The use of a biomacromolecule bound enzyme rather than direct grafting to the surface or nanoparticle bound enzymatic systems allows for scalable production of the devices using standard dip, spray, or spin-coating techniques from aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…To fully apprehend the potential of PIC gels as 3D cell culture systems for various cell types, the precise relationship between gel stiffness, polymer concentration, the presence of adhesive ligands and migration propensity needs to be established and specified per cell subtype. It is important to take into account how gel stability and stiffness change over time, as prolonged use of PIC gels in 3D cell culture will decrease gel stiffness and permit cellular migration ( 41 ).…”
Section: Discussionmentioning
confidence: 99%